Strategi Pengembangan Koperasi Syariah Di Kota Pekanbaru - Veni Angriani; Hasim As'ari (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2021)
Sharia cooperatives are a form of sharia economic development in existing social developments. Cooperatives, especially sharia cooperatives, are synonymous with a populist economic system with a pattern of Islamic religious rules and mutual trust. Pekanbaru is the area with the highest number of sharia cooperatives compared to other areas in Riau Province. The research objective shows that the strategy for developing sharia cooperatives in the city of Pekanbaru and looking at the inhibiting factors for the strategy of Islamic cooperatives through strategies that have been carried out by the Department of Cooperatives and SMEs in the city of Pekanbaru This study uses the strategy theory of Richard Rumlet (2012) which uses 4 indicators, namely: 1). Consistency, 2). Conformity, 3). Excellence, and 4). Appropriateness. This study uses a qualitative method located in Pekanbaru City. In connection with the strategy carried out in the development of sharia cooperatives in Pekanbaru City carried out by the Pekanbaru City Cooperative and UMKM Office, it turns out that it is not serious in its realization, there are still no regulations governing cooperatives in the city of Pekanbaru and there is no strategy implemented to carry out conventional cooperative development strategies.